2-hydroxy-3-phenylpropanoic acid suppressed the growth of Alternaria alternata through damaging cell membrane integrity and modulating reactive oxygen species metabolism. Issue 3 (March 2023) - Liu, Jiaxin; Li, Canying; Zhang, Chenyang; Huang, Rui; Qu, Linhong; Ge, Yonghong
Abstract: Black spot rot caused by Alternaria alternata is one of the major postharvest disease of apple fruit during logistic. This study evaluated in vitro inhibitory effect of 2-hydroxy-3-phenylpropanoic acid (PLA) at various concentrations on A. alternata and the possible mechanisms involved in its action. Results showed that different concentrations of PLA inhibited conidia germination and mycelial growth of A. alternata in vitro, and 1.0 g L −1 was the lowest effective concentration to suppress A. alternata growth. Moreover, PLA significantly reduced relative conductivity and increased malondialdehyde and soluble protein contents. PLA also increased H2 O2 and dehydroascorbic acid contents, but reduced ascorbic acid content. Additionally, PLA treatment inhibited catalase, ascorbate peroxidase, monodehydroascorbate acid reductase, dehydroascorbic acid reductase and glutathione reductase activities, whereas promoted superoxide dismutase activity. All these findings suggest that the possible mechanisms involved in the inhibitory effect of PLA on A. alternata included damaging the cell membrane integrity to cause electrolyte leakage and destroying reactive oxygen species balance. Highlights: 2-hydroxy-3-phenylpropanoic acid inhibited conidia germination and mycelial growth of Alternaria alternata . 2-hydroxy-3-phenylpropanoic acid destroyed the reactive oxygen species balance in A. alternata to inhibit its growth. 2-hydroxy-3-phenylpropanoic acid damaged the cell membrane integrity of A. alternata .